2020
DOI: 10.1111/dth.14509
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells as predictive markers of responsiveness to hydroxychloroquine treatment in primary cicatricial alopecia patients

Abstract: Primary cicatricial alopecia (PCA) encompasses a diverse group of inflammatory diseases characterized by the irreversible replacement of hair follicle structures by fibrous tissue. Although the pathogenesis of PCA remains not fully understood, the key to its understanding might be the location of dendritic cells (DCs) inflammatory infiltrate. One of the systemic therapy of choice in PCA patients is hydroxychloroquine (HCQ). We hypothesized that DCs are implicated in PCA pathogenesis and that they might constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…They reported that 79.3% of patients had disease stabilization with combination therapy [29]. A few other articles we encountered demonstrated either a majority of patients responding to HCQ treatment or FFA stabilization [2, 17, 20, 3033]. Lastly, a study that exclusively examined men with FFA also found halted disease progression with HCQ [34].…”
Section: Frontal Fibrosing Alopeciamentioning
confidence: 94%
See 2 more Smart Citations
“…They reported that 79.3% of patients had disease stabilization with combination therapy [29]. A few other articles we encountered demonstrated either a majority of patients responding to HCQ treatment or FFA stabilization [2, 17, 20, 3033]. Lastly, a study that exclusively examined men with FFA also found halted disease progression with HCQ [34].…”
Section: Frontal Fibrosing Alopeciamentioning
confidence: 94%
“…Cases of lupus panniculitis have shown positive responses and complete resolution in some patients with HCQ treatment [48][49][50][51][52][53][54][55][56][57]. A retrospective cohort study found 66.7% of discoid lupus erythematosus patients responding to HCQ [20]. Two reports of discoid lupus erythematosus patients taking HCQ also exhibited hair regrowth [58,59].…”
Section: Lupus Alopeciamentioning
confidence: 99%
See 1 more Smart Citation